Grammatical Errors Analysis in Descriptive Text Writing - Pujalita Sujiarti; Doni Azhari; Taufiq Kurniawan (Lembaga Pengembangan Kinerja Dosen, 2023)
The purposes of this research were to find out studens’ grammatical errors on writing descriptive text and the possible causes of their grammatical errors. This research used descriptive qualitative method with the 20 participants of IPA MA NW Perian as the sample. Observation, interview, and questionare were used as the research instruments. The result showed that the students produce 44,87 % errors in using verb, 23,07 % errors in using noun, 16,66 % errors in using pronoun, 8,97 % errors in using preposition, and 6,41 % errors in use of adjective. The students produced 44,87 % errors from 78 of total number of errors in writing descriptive text. Based on the result interview and questionnaire the researcher found that most students knew descriptive text definition but frequently found it difficult to write descriptive text since they were still confused in grammar, vocabularies arrangement, and word orders. It was concluded that the possible causes of errors are grammatical, words selection, and word orders.